Redações nota mil do ENEM: um estudo analítico da massificação de sua estrutura e conteúdo - Paiva, Renata Ingrid de Souza (2020)
The context of textual production of the Exame Nacional do Ensino Médio (ENEM) is one of the main mobilizers of the preparatory years for candidates, including with regard to teaching Portuguese in the final years of high school. Based on the impacts caused by the exam, this research aims at the analytical study of the writing of grade one thousand composition, taking as a hypothesis the massification of the structure and content of the texts. The research has the general objective: to investigate how the students' structural and content choices, as well as the use of the other's voice, influence the argumentative logic for the success of the grade one thousand composition. As specific objectives, we delimit: i) to identify the structural and content marks found in the texts and which are presented with greater recurrence; ii) to characterize the use and recurrence, in the analyzed texts, of the insertion of the voice of others; iii) determine, in a comparative way, the functionality of these voices inserted in the argumentative logic of the composition; and iv) show in which aspects the structural, content choices and the insertion of others' voices constitute what we consider as massification. For that, we resort to the contributions of Charaudeau (2009) about the organization of argumentative texts as well as the argumentative logic; Authier-Revuz (1990, 2004) on the reflections of enunciative heterogeneity shown; de Adorno (1985), for the discussion on massification, and Pêcheux (1995) on the subject's position to characterize the place of the speech of the candidate authors in the composition. The corpus consists of 32 (thirty-two) composition, equally spread over four years (2014, 2015, 2016 and 2017). The results show that, in all years, there is a standardization in structure and content that is not attributed to what the five competencies suggest in their entirety, in addition to a recurrence of the use of the explicit insertion of the other's voice to compose the argumentative logic. As for the issue of structural and content massification, we observe that there is a recurrence of the construction of a molded and pre-established “form” of writing so that candidates, in the preparatory years for the exam, activate the need to shape their texts so that they occupy the position of “model” composition, considered here whit the maximum score.